Underlying Co-Morbidity Reveals Unique Immune Signatures in Type II Diabetes Patients Infected With SARS-CoV2 - Sengupta, Soumya; Bhattacharya, Gargee; Chatterjee, Sanchari; Datey, Ankita; Shaw, Shubham K.; Suranjika, Sandhya; Nath, Paritosh; Barik, Prakash K.; Prasad, Punit; Chattopadhyay, Soma; Swain, Rajeeb K.; Parida, Ajay; et al. (Frontiers in Immunology, 2022)
Background SARS-CoV2 infection in patients with comorbidities, particularly T2DM, has been a major challenge globally and has been shown to be associated with high morbidity and mortality. Here, we did whole blood immunophenotyping along with plasma cytokine, chemokine, antibody isotyping, and viral load from oropharyngeal swab to understand the immune pathology in the T2DM patients infected with SARS-CoV2. Methods Blood samples from 25 Covid-19 positive patients having T2DM, 10 Covid-19 positive patients not having T2DM, and 10 Covid-19 negative, non-diabetic healthy controls were assessed for various immune cells by analyzing for their signature surface proteins in mass cytometry. Circulating cytokines, chemokines, and antibody isotypes were determined from plasma while viral copy number was determined from oropharyngeal swabs. All our representative data corroborated with laboratory findings. Results Our observations encompass T2DM patients having elevated levels of both type I and type II cytokines and higher levels of circulating IgA, IgM, IgG1, and IgG2 as compared to NDM and healthy volunteers. They also displayed higher percentages of granulocytes, mDCs, plasmablasts, Th2-like cells, CD4+ EM cells, and CD8+ TE cells as compared to healthy volunteers. T2DM patients also displayed lower percentages of pDCs, lymphocytes, CD8+ TE cells, CD4+, and CD8+ EM. Conclusion Our study demonstrated that patients with T2DM displayed higher inflammatory markers and a dysregulated anti-viral and anti-inflammatory response when compared to NDM and healthy controls and the dysregulated immune response may be attributed to meta inflammation.